2019
DOI: 10.1016/j.renene.2018.08.101
|View full text |Cite
|
Sign up to set email alerts
|

New approach for solar tracking systems based on computer vision, low cost hardware and deep learning

Abstract: In this work, a new approach for Sun tracking systems is presented. Due to the current system limitations regarding costs and operational problems, a new approach based on low cost, computer vision open hardware and deep learning has been developed. The preliminary tests carried out successfully in Plataforma solar de Almería (PSA), reveal the great potential and show the new approach as a good alternative to traditional systems. The proposed approach can provide key variables for the Sun tracking system contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 22 publications
0
12
0
4
Order By: Relevance
“…Various studies have recommended and demonstrated successfully the use of pre-trained network models. 3137 In the present study, the feature extraction properties of several renowned CNN architectures like VGG 16, 18 GoogLeNet, 38 AlexNet, 17 and ResNet50 20 were evaluated with the help of machine learning classifiers. A brief description of the CNN models considered are described in this section.…”
Section: Machine Learning Based Three Phase Approach For Fault Detection In Aerial Imagesmentioning
confidence: 99%
“…Various studies have recommended and demonstrated successfully the use of pre-trained network models. 3137 In the present study, the feature extraction properties of several renowned CNN architectures like VGG 16, 18 GoogLeNet, 38 AlexNet, 17 and ResNet50 20 were evaluated with the help of machine learning classifiers. A brief description of the CNN models considered are described in this section.…”
Section: Machine Learning Based Three Phase Approach For Fault Detection In Aerial Imagesmentioning
confidence: 99%
“…The proposed system captures reflections from the target and uses image processing to detect and extract solar angles based on BP neural networks. Carballo et al [55] developed a low-cost machine vision solar tracking system that can be used for Using the same concept, Berenguel et al [50] proposed a model to correct the calculation and installation of the solar position. The model is based on the use of a charge-device camera to capture images of the reflected beams from each field heliostat to the target to be used for offset correction.…”
Section: Review Of Tracking Systems For Crsmentioning
confidence: 99%
“…The proposed system captures reflections from the target and uses image processing to detect and extract solar angles based on BP neural networks. Carballo et al [55] developed a low-cost machine vision solar tracking system that can be used for any type of solar system. The proposed system calculates the Sun vector, the target vector of the receiver and the aiming point vector on a camera plane below the receiver tower.…”
Section: Review Of Tracking Systems For Crsmentioning
confidence: 99%
“…Bobot telur ayam diperoleh dari perhitungan luasan hasil segmentasi telur ayam yang dihasilkan. Disisi lain, pencitraan nyala lampu dapat dianalogikan dengan pencitraan sinar matahari [7,10,11]. Keduanya menggunakan thresholding untuk mendapatkan citra sinar matahari.…”
Section: Pendahuluanunclassified